2014
DOI: 10.1890/13-1416.1
|View full text |Cite
|
Sign up to set email alerts
|

Biological soil crusts across disturbance–recovery scenarios: effect of grazing regime on community dynamics

Abstract: Grazing represents one of the most common disturbances in drylands worldwide, affecting both ecosystem structure and functioning. Despite the efforts to understand the nature and magnitude of grazing effects on ecosystem components and processes, contrasting results continue to arise. This is particularly remarkable for the biological soil crust (BSC) communities (i.e., cyanobacteria, lichens, and bryophytes), which play an important role in soil dynamics. Here we evaluated simultaneously the effect of grazing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 60 publications
5
41
3
Order By: Relevance
“…The response of LC and DC to grazing that we observed in the low aridity site contradicts the results found by Concostrina-Zubiri et al (2014), who described a positive response of cyanobacteria-dominated biocrusts to grazing in Mexico. The response of LC and DC to grazing that we observed in the low aridity site contradicts the results found by Concostrina-Zubiri et al (2014), who described a positive response of cyanobacteria-dominated biocrusts to grazing in Mexico.…”
Section: Grazing Interacts With Aridity To Determine Biocrust Biomacontrasting
confidence: 99%
See 1 more Smart Citation
“…The response of LC and DC to grazing that we observed in the low aridity site contradicts the results found by Concostrina-Zubiri et al (2014), who described a positive response of cyanobacteria-dominated biocrusts to grazing in Mexico. The response of LC and DC to grazing that we observed in the low aridity site contradicts the results found by Concostrina-Zubiri et al (2014), who described a positive response of cyanobacteria-dominated biocrusts to grazing in Mexico.…”
Section: Grazing Interacts With Aridity To Determine Biocrust Biomacontrasting
confidence: 99%
“…Our work also widens the knowledge of the biology and ecology of biocrusts in South America, thus fulfilling an existing geographical gap . Crustose and squamulose morphologies, such as those found in this site, can provide lichens with partial resistance to mechanical impact (Concostrina-Zubiri et al, 2014;Jiménez Aguilar et al, 2009). However, and contrary to our expectations, biocrust biomass responses to grazing intensity were similar under light-grazed (LG) and high-grazed (HG) conditions in the low aridity site.…”
Section: Grazing Interacts With Aridity To Determine Biocrust Biomacontrasting
confidence: 88%
“…23.1, this is likely an oversimplification even of the general sequence. A recent study conducted in the Chihuahuan Desert of Mexico provides additional evidence of multiple successional trajectories (Concostrina-Zubiri et al 2014). The authors compared biocrusts of rangelands in exclosures released for 11 and 27 years from continuous high-intensity grazing and released for 6 years from seasonal high-intensity grazing.…”
Section: Multiple Successional Pathwaysmentioning
confidence: 99%
“…Studies dealing with the effect of land use on BSCs were mainly conducted in arid and semiarid regions. These studies showed strong negative effects of intensive livestock grazing on BSC cover due to trampling and reported a subsequent BSC recovery period of up to 27 years (Concostrina-Zubiri et al, 2014;Gomez et al, 2004;Williams et al, 2008). Also, ploughing in Australian sand plains reduced the BSC cover dramatically (Daryanto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%